2021
DOI: 10.1101/2021.03.22.21253577
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Demographic and clinical features associated with in-hospital mortality in Egyptian COVID-19 patients: A retrospective cohort study

Abstract: Introduction: Since the worldwide emergence of the COVID-19, several protocols were used by different healthcare organisations. We evaluated in this study the demographic and clinical characteristics of COVID-19 disease in Egyptian population with special consideration for its mortality predictors. Methodology: 8162 participants (mean age 48.7 years,54.5% males) with RT-PCR positive COVID-19 were included. The electronic medical records were reviewed for demographic, clinical, laboratory, and radiologic featur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In the current study, the optimum cut-off point that could predict severe COVID-19 infection was > 8. A large cohort study on similar population found a statistically significant strong association of in-hospital mortality with neutrophil-lymphocyte ratio > 3.1 [28]. The lack of a single universal definition for severe COVID-19 infection and the variable outcome measures used in different studies could explain this wide range and variances.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the optimum cut-off point that could predict severe COVID-19 infection was > 8. A large cohort study on similar population found a statistically significant strong association of in-hospital mortality with neutrophil-lymphocyte ratio > 3.1 [28]. The lack of a single universal definition for severe COVID-19 infection and the variable outcome measures used in different studies could explain this wide range and variances.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and medical information were abstracted from the patient's files and included age, sex, body weight, cigarette smoking status, medical history, and medications. All the patients received treatment according to the Egyptian COVID-19 treatment protocol (Table 1) established by the Egyptian Ministry of Health (Masoud et al, 2020). Whole blood samples (3 mL) were collected for DNA extraction and genotyping.…”
Section: Study Design and Populationmentioning
confidence: 99%